2021
DOI: 10.3389/fcell.2021.739358
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Related SPP1 as a Potential Biomarker for Early Lymph Node Metastasis in Lung Adenocarcinoma

Abstract: Lymph node metastasis is a major factor that affects prognosis in patients with lung adenocarcinoma (LUAD). In some cases, lymph node metastasis has already occurred when the primary tumors are still small (i.e., early T stages), however, relevant studies on early lymph node metastasis are limited, and effective biomarkers remain lacking. This study aimed to explore new molecular biomarker for early lymph node metastasis in LUAD using transcriptome sequencing and experimental validation. Here, we performed tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…These data indicate that M1 macrophages might play a role in BC rupture, whereas M2 macrophages increase at the late stage of the disease, which might contribute to fibrosis. In addition, we found that the RNA and protein expression levels of CD163 increased significantly when the BC ruptured, together with the increased expression of SPP1, which was reported to be significantly correlated with macrophage infiltration and M2 polarization ( 15 ). It was previously reported that both the high expression of SPP1 and that of its receptor CD44 correlated with an increased macrophagic infiltration ( 27 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These data indicate that M1 macrophages might play a role in BC rupture, whereas M2 macrophages increase at the late stage of the disease, which might contribute to fibrosis. In addition, we found that the RNA and protein expression levels of CD163 increased significantly when the BC ruptured, together with the increased expression of SPP1, which was reported to be significantly correlated with macrophage infiltration and M2 polarization ( 15 ). It was previously reported that both the high expression of SPP1 and that of its receptor CD44 correlated with an increased macrophagic infiltration ( 27 ).…”
Section: Discussionmentioning
confidence: 94%
“…The above results highlighted the critical role of SPP1 in glomerulosclerosis and possibly in fibrous crescent formation. Moreover, SPP1 is known to mediate M2-type macrophage polarization ( 14 ), which also plays a role in fibrosis ( 15 , 16 ). Our data showed that the expression of CD163 gradually increased with worsening of the glomerular injury ( Figure 3I ), and SPP1, together with its receptor CD44, strongly correlated with CD163 (an M2-type macrophage marker; r = 0.8328, p < 0.0001; r = 0.7231, p < 0.0001, respectively) ( Figures 3J, L ), but not with CD86 expression (an M1-type macrophage marker; r = 0.1856, p = 0.2121) ( Figure 3K ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence showed that SPP1 mediates macrophage polarization through the upregulation of PD‐L1 and promotes immune escape in lung adenocarcinoma 28 . Thus, as a hallmark gene of epithelial‐mesenchymal transition, SPP1 was significantly correlated with macrophage infiltration and M2 polarization and was thought to be a key risk predictor for early LNM in cancer development 29 . Besides cancers, SPP1 might have a correlation with the infiltration of M2 macrophages in prostatic intraepithelial neoplasia lesions (a type of precancerous lesions), and high levels of SPP1 could be detected in these macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…28 Thus, as a hallmark gene of epithelialmesenchymal transition, SPP1 was significantly correlated with macrophage infiltration and M2 polarization and was thought to be a key risk predictor for early LNM in cancer development. 29 Besides cancers, SPP1 might have a correlation with the infiltration of M2 macrophages in prostatic intraepithelial neoplasia lesions (a type of precancerous lesions), and high levels of SPP1 could be detected in these macrophages. Under this tumor microenvironment, SPP1 may stimulate the malignant transformation in the lesions by activating Akt and JNK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%